2020
DOI: 10.1016/j.fct.2020.111330
|View full text |Cite
|
Sign up to set email alerts
|

Enriched feeds with iodine and selenium from natural and sustainable sources to modulate farmed gilthead seabream (Sparus aurata) and common carp (Cyprinus carpio) fillets elemental nutritional value

Abstract: Barbosa et al. (2020). Enriched feeds with iodine and selenium from natural and sustainable sources to modulate farmed gilthead seabream (Sparus aurata) and common carp (Cyprinus carpio) fillets elemental nutritional value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…However, these fatty acids were at very low or undetectable levels in the diets, like eicosadienoic acid type. This fact demonstrates that gurami sago, similar to other freshwater fish species, such as Oreochromis niloticus 61 and Cyprinus carpio 21 , can elongate and desaturate fatty acids from precursors present in the diet, including 18C:0 fatty acids and possibly from linoleic fatty acid in large quantities from the diets.…”
Section: Effect Of Different Formulation Products On the Fatty Acid Profile Of The Dietsmentioning
confidence: 78%
See 2 more Smart Citations
“…However, these fatty acids were at very low or undetectable levels in the diets, like eicosadienoic acid type. This fact demonstrates that gurami sago, similar to other freshwater fish species, such as Oreochromis niloticus 61 and Cyprinus carpio 21 , can elongate and desaturate fatty acids from precursors present in the diet, including 18C:0 fatty acids and possibly from linoleic fatty acid in large quantities from the diets.…”
Section: Effect Of Different Formulation Products On the Fatty Acid Profile Of The Dietsmentioning
confidence: 78%
“…Different strategies have been developed to improve aquafeed nutrition, including enriching feed with fish oil 9,19 , soybean oil 20 , iodine and selenium 21 , EPA and DHA 22 , and the use of probiotics 23 . The goal is to make the diet rich in nutrients such as amino acids, fatty acids, minerals, and vitamins because the animal cannot synthesize them in sufficient quantities to meet their needs 17,24,25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, fish fed the diets supplemented with selenised yeast were able to increasingly retain the ingested selenium and accumulate it in their bodies. In a complementary study, with the same enriched feeds, it was demonstrated that the dietary supplementation with 0.02% selenised yeast was enough to achieve higher selenium contents in seabream filets compared with CTRL (0.23–0.36 μg g –1 in AD diets vs. 0.18 μg g –1 in CTRL), without increasing consumer’s exposure to toxic elements ( Barbosa et al, 2020 ). Together, these results indicate that organic selenium provided by selenised yeast is an effective vehicle to fortify gilthead seabream filets.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine and selenium contents of feed samples were determined according to the European standards EN 15111:2007 and EN 15763:2009, respectively. Inductively coupled plasma mass spectrometer (ICP-MS) (Thermo X series II, Thermo Fisher Scientific, Waltham, United States), after alkaline (iodine) or acid (selenium) digestion, was used for determination of iodine and selenium, as described by Barbosa et al (2020) .…”
Section: Methodsmentioning
confidence: 99%